Digitization and Open Access of the Proceedings of the Geoscience Information Society. Issue 1 (2nd January 2017) - Kimball, Rusty
ABSTRACT: The Geoscience Information Society (GIS, later GSIS) was established at the 1965 meeting of the Geological Society of America (GSA) as an associated society of GSA and is dedicated to improving the exchange of information among geosciences librarians and other professionals. GSIS meetings from 1966 to 2012 have generated forty-three proceedings volumes. An agreement between GSIS and Texas Digital Libraries member Texas A&M University Libraries established that all of the GSIS Proceedings would be hosted on the Libraries' Institutional Repository, OakTrust, as open access. All digital and scanned proceedings volumes PDFs were carefully deposited with standardized metadata into OakTrust, with all future GSIS Proceedings volumes to follow.